2020
DOI: 10.1007/s10792-020-01482-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of fasting on intraocular pressure, anterior segment parameters and density of crystalline lens and cornea

Abstract: Purpose To evaluate the effect of fasting on anterior chamber depth, anterior chamber volume and corneal and lens density by Scheimpflug technology and to measure intraocular pressure changes. Methods Totals of 50 healthy fasting individuals in Ramadan (study group) and 50 healthy non-fasting subjects (control group) were included. Central corneal thickness (CCT), anterior chamber depth (ACD), anterior chamber volume (ACV), corneal density (CD) and lens density (LD) were evaluated with Scheimpflug technology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Intermittent fasting alters anterior chamber depth and volume, which is mostly due to dehydration This difference may be noticed in both fasting and non-fasting groups, and at various moments during the fasting period. Compared to the non-fasting group, anterior chamber depth and axial length were dramatically reduced in the fasted group ( 34 , 47 ). Furthermore, during IF, the depth and volume of the anterior chamber were variable at different times of the day.…”
Section: Intermittent Fasting and Ocular Biological Parametersmentioning
confidence: 83%
See 4 more Smart Citations
“…Intermittent fasting alters anterior chamber depth and volume, which is mostly due to dehydration This difference may be noticed in both fasting and non-fasting groups, and at various moments during the fasting period. Compared to the non-fasting group, anterior chamber depth and axial length were dramatically reduced in the fasted group ( 34 , 47 ). Furthermore, during IF, the depth and volume of the anterior chamber were variable at different times of the day.…”
Section: Intermittent Fasting and Ocular Biological Parametersmentioning
confidence: 83%
“…Norepinephrine and cortisol produced during sympathetic excitation are elevated, and resistance to atrial outflow increases, causing IOP to rise. However, most studies have shown a significant decrease in IOP values during IF ( 34 , 39 44 ). Kerimoglu et al ( 42 ) found that in the Ramadan fasting population, IOP tended to be higher in the morning (fasting vs. non-fasting: 14.19 ± 3.53 mmHg vs. 12.03 ± 2.99 mmHg) and lower in the afternoon (fasting vs. non-fasting: 11.74 ± 2.39 mmHg vs. 13.13 ± 2.39 mmHg).…”
Section: Intermittent Fasting and Ocular Biological Parametersmentioning
confidence: 97%
See 3 more Smart Citations